Pengaruh Viral Marketing dan Fear of Missing Out Terhadap Keputusan Pembelian Pada Produk Parfum H.M.N.S di Garut - Rismanto Hilman; Anwil Wafa Syawaludin; Arsyi Fauzan; Mardhan Muhammad Ramdani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study focuses on examining the effect of Viral Marketing and Fear of Missing Out (FOMO) on consumer purchase decisions for H.M.N.S perfume products in Garut. The research background is driven by the rapid development of digital media that has transformed consumer behavior, where viral marketing strategies and psychological drivers such as FOMO increasingly influence purchasing decisions. The purpose of this study is to analyze the influence of Viral Marketing and FOMO on consumer purchase decisions. The research employed a quantitative approach with data collected through questionnaires from 100 respondents, and data were analyzed using Partial Least Squares (PLS) to test validity, reliability, and relationships among variables. The results indicate that Viral Marketing and FOMO significantly influence Purchase Decisions for H.M.N.S perfume products, with path coefficients of 0.329 (positive effect) and 0.178 (positive effect), respectively. The adjusted R-squared value of 0.178 indicates that the independent variables explain 17.8% of the variance in Purchase Decisions, while the remaining 82.2% is influenced by other factors outside the model. The findings emphasize the importance for companies to enhance sales not only through digital marketing strategies delivered via influencers and digital media environments, but also through psychological factors such as fear of missing out, which reflects consumers’ desire to own popular products and may lead to anxiety and compulsive purchasing behavior within a purchase decision framework in the context of local perfume products.